Prevalence of sleep disturbances in endometriosis patients: a systematic review and meta-analysis - Zhang, Yujie; Liu, Hui; Feng, Chaochen; Yang, Yadi; Cui, Liwei (Frontiers in Psychiatry, 2024)
Objective: This study systematically analyzes the prevalence of sleep disturbance in patients with endometriosis. Methods: The PubMed, Web of Science, Embase, Wanfang, China National Knowledge Internet Database (CNKI), China Science and Technology Journal Database were searched from their establishment to January 2024, using the search terms endometriosis and sleep disturbance to collect relevant literature on the prevalence of sleep disturbance in patients with endometriosis. Two researchers independently screened the literature, extracted data, and evaluated the risk of bias. The prevalence of sleep disorders in patients with endometriosis was systematically analyzed using Stata17.0 software. Results: Sixteen studies with 2573 participants were included. The prevalence of sleep disturbance in patients with endometriosis was 70.8% (95% confidence interval: 60.7%~80.9%). The said prevalence was higher in China than in Iran and the European countries (78.2 vs. 57.6 vs. 64.4, Q=9.27, P=0.010) and increased significantly since 2018 (79.0 vs. 61.3, Q=3.97, P=0.046). This prevalence was significantly higher in the cohort study than that in cross-sectional and case-control studies (84.0 vs. 74.0 vs. 59.5, Q=7.16, P=0.028). Conclusion: The prevalence of sleep disturbance is high in patients with endometriosis, particularly in China and its prevalence has increased significantly in recent years. Appropriate interventions are recommended to effectively prevent or minimize sleep disturbances in patients with endometriosis.